Mr. Hynde is out of his mind! - Gutman, Dan (Gutman, Dan. My weird school, 2005)
When boring Mr. Loring retires, A.J.'s class gets a new music teacher who raps, break-dances, and thinks he has what it takes to become a famous musician.